Numerical investigation of a novel manifold micro-pin-fin heat sink combining chessboard nozzle-jet concept for ultra-high heat flux removal. (November 2018) - Ju, Xing; Xu, Chao; Zhou, Yiting; Liao, Zhirong; Yang, Yongping
Highlights: A novel manifold chessboard nozzle-jet micro-pin-fin heat sink is proposed. Influences of geometric parameters are studied to achieve optimized design. Different configurations of the heat sink are also compared. Hydrodynamic and thermal characteristics are analyzed in details. Abstract: In this paper, a novel heat sink combining the manifold flow distributor, impinging nozzle-jet, and micro-pin-fin concepts is proposed. The flow distribution structure of the heat sink is inspired by black and white fields of the chessboard. Every inlet nozzle is surrounded by four outlet nozzles and vice versa. A 3-dimensional numerical simulation model of the basic heat sink structure is introduced to investigate the thermal and hydrodynamic performances. Several configurations with different pin-fin and nozzle geometries and its sensitivity to the geometrical parameters are discussed for optimization. Designs with different numbers of pin-fins in the unit cell of heat sink are also compared. The results show that, for a 2 × 2 cm 2 chip or photovoltaic, a total thermal resistance of 9.37 × 10 −6 Km 2 /W is achieved at a flow rate of 1 L/min and a pressure drop of 4928 Pa. A maximum cooling capacity of 700 W/cm 2 can be satisfied with the temperature difference between the fluid inlet and chip of 65.5 K, and the temperature non-uniformity of the heating surface of only 2.33 K. The numerical results indicate that the novel heat sink shows great advantages of both uniform flow distribution and ultra-high heat flux cooling.